2018
DOI: 10.1002/hed.25347
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of small monitoring skin paddle in free muscle flap for scalp reconstruction

Abstract: The efficacy of flap monitoring and flap salvage outcomes were improved by including a small monitoring skin flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(128 reference statements)
0
1
0
1
Order By: Relevance
“…These findings are all the more significant in view of the vulnerable patient cohort, with a mean age of 62 years and a history of carcinoma. The skin paddle method has also been shown to be effective in scalp reconstruction: Park et al reported significantly higher FF salvage rates and total FF survival when compared to conventional monitoring strategies (108). Again, the average patient was older than 62 years and the etiology was predominantly tumor-related.…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…These findings are all the more significant in view of the vulnerable patient cohort, with a mean age of 62 years and a history of carcinoma. The skin paddle method has also been shown to be effective in scalp reconstruction: Park et al reported significantly higher FF salvage rates and total FF survival when compared to conventional monitoring strategies (108). Again, the average patient was older than 62 years and the etiology was predominantly tumor-related.…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…Im Gegensatz hierzu werden Muskellappenplastiken mit Spalthaut transplantiert und weisen somit keinen rekapillarisierbaren Hautanteil zur klinischen Kontrolle auf. Um dennoch eine klinische Beurteilung von Muskellappenplastiken zu ermöglichen, werden diese standardmäßig mitsamt einer randomisiert durchbluteten, adipokutanen Monitorinsel gehoben, deren Kapillarbett vom darunterliegenden Muskelgewebe versorgt wird 22 , 23 . Mit Ausnahme der Monitorinsel wird der restliche Muskel mit Spalthaut transplantiert.…”
Section: Introductionunclassified